Enhancing phosphorus bioavailability in sewage sludge through co-hydrothermal treatment with biomass. (February 2023) - Li, Jiawei; Jin, Jie; Zhao, Yunao; Zou, Ziwei; Wu, Yunchao; Sun, Jintao; Xia, Jinxia
Abstract: The renewable utilization of phosphorus (P) in sewage sludge is greatly hindered by its low bioavailability. In this study, the co-hydrothermal treatment (co-HTT) of sewage sludge and biomass was conducted to enhance P bioavailability. The dehydration and decarboxylation of sludge organic matter were promoted by co-HTT as evidenced by FTIR and elemental analysis. XPS and XRD results showed that co-HTT facilitated the formation of Al/Fe phosphates in sludge. The results of Hedley's sequential extraction demonstrated that HTT at low temperatures (≤ 155 °C) enlarged the relative abundance of bioavailable P in the sludge from 72 % to as high as 80 % because of the decomposition of organic P. In contrast, at a high temperature of 185 °C, more bioavailable P was converted into insoluble and residual forms. The addition of rice straw in sludge during HTT resulted in a two-fold increase in exchangeable P content, suggesting that rice straw can effectively improve sludge P bioavailability. Cellulose exhibited less influence on sludge P bioavailability than lignin. After lignin addition, the relative abundance of bioavailable P in the sludge was further increased to 91 %, which could be attributed to the greater enhancement effect of lignin on the decomposition of sludge organic matter. These findings reveal that the co-HTT of sludge and lignin-containing biomass may be an effective strategy for improving sludge P bioavailability. Highlights: The co-hydrolysis of sludge and biomass was applied to enhance P bioavailability. HTT at low temperature increased the amount of bioavailable P. The addition of rice straw in HTT promoted the formation of exchangeable P. Lignin had a stronger effect on enhancing sludge P availability than cellulose.